Dental procedures in children with or without intellectual disability and autism spectrum disorder in a hospital setting. (3rd July 2022) - Azimi, S; Wong, K; Lai, YYL; Bourke, J; Junaid, M; Jones, J; Pritchard, D; Calache, H; Winters, J; Slack‐Smith, L; Leonard, H
Abstract: Background: This population‐based cohort study investigated dental procedures in the hospital setting in Western Australian children with or without intellectual disability (ID) and/or autism spectrum disorder (ASD) aged up to 18 years. Considering previously reported disparities in dental disease between Indigenous and non‐Indigenous Australian children, this study also investigated the effect of Indigenous status on dental procedures. Methods: Data on Western Australian live births from 1983 to 2010 from the Midwives Notification System were linked to the Intellectual Disability Exploring Answers database and the Hospital Morbidity Data collection. Primary admissions for relevant dental diagnoses were identified, and treatment procedures for dental hospitalization were investigated. Descriptive statistics and Pearson's chi‐squared test of independence were used for analysis. Results: Overall, 76 065 episodes of dental hospitalization were recorded. Amongst children with ID and/or ASD, Indigenous children experienced more extractions and fewer restorations (68.7% and 16.2%) compared to non‐Indigenous children (51.5% and 25.9%). After 6 years, extraction occurred less often in children with ID and/or ASD than in those without, where most surgical dental extractions were in the age group of 13–18 years. Conclusions: This study indicates a need for further improvements in access to dental services and the quality of care provided in hospitals for children with ID/ASD. There is also concern that more vulnerable Indigenous and all disadvantaged children are receiving an inadequate level of dental services resulting in more emergency dental hospitalization and invasive treatment.